Ancient Coins in the Collection of the Jan Kasprowicz Museum in Inowrocław - Jarzęcki, Krzysztof (Acta Archaeologica Lodziensia, 2021)
The article concerns 23 ancient coins (8 Greek, 1 Numidian, and 14 Roman) from the museum collection in Inowrocław. One coin comes from archaeological excavations (a Trajanic denarius type RIC 6), the rest from donations and purchases. The coins donated to the museum are chance finds, however the donors indicated the place where they were found. The remaining coins have been purchased from old collections. In one case their previous owner is known: Kazimierz Miaskowski (1875-1947), a catholic priest, and author of many publications associated with the Inowrocław region. The land around Inowrocław stands out as an area in which many ancient coins have been found. The author analyses coins from the museum against the background of finds from the Inowrocław area. Many of the coins in the collection are likely to have been found in the immediate area of the town. The author also tries to reconstruct the collections from which they came, and the fate of these collections